Glycosylation of bacterial antigens changes epitope patterns - Kern, Karolin; Delaroque, Nicolas; Boysen, Anders; Puder, Marcus; Wendt, Ralph; Kölsch, Andreas; Ehrentreich-Förster, Eva; Stærk, Kristian; Andersen, Thomas Emil; Andersen, Karin; Lund, Lars; Szardenings, Michael (Frontiers in Immunology, 2023)
Introduction: Unlike glycosylation of proteins expressed in mammalian systems, bacterial glycosylation is often neglected in the development of recombinant vaccines. Methods: Here, we compared the effects of glycosylation of YghJ, an E. coli protein important for mucus attachment of bacteria causing in urinary tract infections (UTI). A novel method based on statistical evaluation of phage display for the identification and comparison of epitopes and mimotopes of anti-YghJ antibodies in the sera was used. This is the first time that the effect of glycosylation of a recombinant bacterial antigen has been studied at the peptide epitope level. Results: The study identifies differences in the immune response for (non)-glycosylated antigens in rabbits and pigs and compares them to a large group of patients with UTI, which have been diagnosed as positive for various bacterial pathogens. We identified glycosylation-specific peptide epitopes, a large immunological similarity between different UTI pathogens, and a broad peptide epitope pattern in patients and animals, which could result in a variable response in patients upon vaccination. Discussion: This epitope analysis indicates that the vaccination of rabbits and pigs raises antibodies that translate well into the human immune system. This study underlines the importance of glycosylation in bacterial vaccines and provides detailed immune diagnostic methods to understand individual immune responses to vaccines 1